Analysis Risk Factors For Suicidal Thoughts Among Students In Surakarta: A Case Study Approach - Siti Khadijah; Sumardino Sumardino; Ah Yusuf; Hanik Endang Nihayati (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The design of this study was a qualitative case study. The inclusion criteria were students with a positive risk of suicide and high scores at the screening phase. Data were obtained by semi-structured interviews and analyzed thematically using the Colaizzi method. This study showed that the exploration of the risk factors for suicidal thoughts consisted of two themes, eight sub-themes, 25 categories, and 50 keywords. Two themes are suicide, and spiritual. Eight sub-themes namely Causes, Response to problems, Family attitude, Efforts that have been made, Obstacle factors, Supporting factors, Meaning of the problem faced, A feeling that arose spiritually. The risk factors for suicidal thoughts among students in Surakarta are that they have no interest in entering higher education, have difficulty in attending lectures, disappointing academic scores, broken home families, problems with a partner, financial issues, sadness, and disappointment in God, and they face problems repeatedly